(untitled) (Damascus University Journal for engineering sciences, 2025)
In this research paper, the unit cost of industrial water in Syria was calculated based on investment costs which amounted to 1330 SP/m3. The efficiency of industrial water use tariffs was evaluated. The research included the water tariff applied to factories located inside and outside the industrial cities. It has been found that there is a large gap between the water tariff applied in Syria and its actual cost. The recovery rate reached (9%) outside the industrial cities, and in the range of (15-17) % for the investment costs inside the industrial cities. The reason for this is that the tariff does not keep pace with the actual costs of produced water. The research showed the inadequacy of the applied tariff in reducing the excessive use of water. The tariff did not take into account the opportunity cost and the cost of economic and environmental externalities. Therefore, the design of water tariff must be reconsidered to achieve efficiency, increase the recovery rate, and apply the progressive segments effectively to reduce excessive water use. The results of this research paper can contribute to raising the economic efficiency of water use and preserving it for future generations.